Ectoparasites (ticks and mites) prevalence on small to medium-sized mammals associated with habitat condition in Kemasul, Pahang - Nor Bazilah Razali,; Nurshahira Shamsudin,; Rahaniza Ali Mohd Jobran,; Salmah Yaakop,; Khoo, Jing Jing; Farah Shafawati Mohd Taib, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2018)
Ectoparasites of small mammals and medium mammals are divided into two main classes which are Insecta and Arachnida. The members of the class Arachnida including order Ixodida (ticks) and Mesostigmata (mites) meanwhile class Insecta comprising Phthiraptera (lice) and Siphonaptera (fleas). This study was conducted to determine tick’s and mite’s prevalence on the small to medium-sized mammals in Kemasul Forest Reserve, Pahang. This forest has undergone rapid deforestation for agricultural purposes. Two study sites were chosen which represented by a forest remnant surrounded with different matrix of monoculture plantation; Jambu Rias (JR) (Elaeis guineensis) and Chemomoi (CM) (Acacia mangium). Three hundred wired mesh cage traps sized (28 cm × 15 cm × 12.5 cm) and forty wired mesh cage traps sized (60 cm × 40 cm × 40 cm) were deployed at the study area and ectoparasites were extracted from each host using a fine comb. Identification was based on morphology and molecular using cytochrome oxidase 1 for confirmation. Mites only represented by Laelaps sp. which shows 95% and 70% prevalence in JR and CM respectively. Ticks were represented by five species, namely Ixodes granulatus, Dermacentor atrosignatus, Rhipicephalus sanguineus, Amblyomma testudinarium and Haemaphysalis sp. JR comprise of five species while CM with two species. I. granulatus was the most common infesting the small mammals in both sites. The highest parasite load was found on small mammals which were Maxomys surifer, M. rajah and M. whiteheadi in both study sites, particularly with mites. The study indicates that habitat condition significantly affects parasite prevalence in small to medium-sized mammal population, which could be due to the resilience of an individual to persist in disturbed habitat.